2009
DOI: 10.1027/1016-9040.14.4.320
|View full text |Cite
|
Sign up to set email alerts
|

Infant Coping and Maternal Interactive Behavior Predict Attachment in a Portuguese Sample of Healthy Preterm Infants

Abstract: In this longitudinal study of a Portuguese sample of healthy preterm infants, the aim was to identify specific, independent predictors of infant-mother attachment status from a set of variables including maternal education, maternal representations’ of infant temperament, infant regulatory behavior (coping), and mothers’ interactive behavior in free play. The sample consisted of 48 medically low-risk preterm infants and their mothers who varied in education. When infants were 1 and 3 months (corrected age), mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
46
1
20

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 41 publications
3
46
1
20
Order By: Relevance
“…Fuertes et al (2009) found that at 3-months infant coping predict patterns of attachment at 12 months. In our study at 3-months, both infant Positive Other-Direct coping and Self-Direct coping were predicted by specific maternal types of interactive behaviour.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Fuertes et al (2009) found that at 3-months infant coping predict patterns of attachment at 12 months. In our study at 3-months, both infant Positive Other-Direct coping and Self-Direct coping were predicted by specific maternal types of interactive behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…It is seems that this Self-Direct coping is more related with maternal intrusivity and over control than from neonatal status. Since past studies found that infant Self Coping Style predicts insecureavoidant attachment (Fuertes et al, 2009), we speculate that this type of arousal regulation it is an early protective strategy that may lead to a defensive and avoidant behaviour.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations